Legal Effects of Credit Agreement Restructuring on Collateral in an Effort to Rescue Non-Performing Loans - Dahris Siregar (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2024)
Credit agreements sometimes arise factors that cause installment payments that have been agreed by the parties are not smooth and can make the banking economy less healthy, because it is undeniable that funds at the bank are also funds owned by customers. This can be said to be a non-performing credit at a bank. When the Credit Agreement is problematic, the bank will work to fix the credit issue as the creditor so that the funds that have been issued by the creditor can be received back based on the guidelines of the loan arrangement. This study's method of research is normative juridical with a concept and law strategy. The results of the study stated that the outcomes attained from causing variables non-performing loans could occur from internal (bank), and outside (debtor) elements. By credit restructuring, it is possible to select it since it may provide both parties superior answers, due to the fact that parties negotiate before it so that both sides' interests are represented.